Click, clack, moo : cows that type - Cronin, Doreen; Lewin, Betsy (New York : Simon & Schuster Books for Young Readers, 2000)
When Farmer Brown's cows find a typewriter in the barn they start making demands, and go on strike when the farmer refuses to give them what they want.
Caldecott Medal/Honor.
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), August 2001.
Booklist, March 2001.
Bulletin (Center for Children's books), September 2000.
Keywords: Cows -- Juvenile fiction; Domestic animals -- Juvenile fiction; Typewriters -- Juvenile fiction; Cows -- Fiction; Domestic animals -- Fiction; Typewriters -- Fiction; Cattle -- Fiction; Domestic animals -- Fiction; Typewriters -- Fiction